Judicial lawmaking and judicial reform: Theoretical and practical aspects of the relationship - Y. Kryvytskyi (Юридичний часопис Національної академії внутрішніх справ, 2024)
The intensification of legal development, increased interpenetration of legal systems, and transformation of legal and state phenomena in the context of globalisation and integration processes necessitate the investigation of the nature of judicial lawmaking and judicial reform and their correlation. The purpose of this study was to theorise the relationship between judicial lawmaking and judicial reform. This study was based on the historical, formal legal, and comparative methods employed in the context of natural law, positivist, sociological approaches, integrative type of legal understanding, theories of lawmaking and justice. The principal findings of this study lie in substantiation of a series of theoretical provisions on judicial lawmaking and judicial reform. It was found that the legal nature of judicial lawmaking is profound and multifaceted. Judicial lawmaking and judicial reform are closely interrelated. One of the manifestations of this interaction is that the introduction of judicial lawmaking is a task, vector, or result of judicial reform. The study proved that judicial lawmaking is a significant achievement of judicial reform, and not a side effect of the transformation of the judicial system. Judicial lawmaking is an essential factor that substantially affects judicial reform in material, procedural, and organisational aspects. Judicial reform, as an independent type of state transformation, is a crucial area of state- building and is aimed at transforming justice into a fair mechanism for resolving legal conflicts and disputes based on the rule of law. With each stage of judicial reform in Ukraine, the need for official recognition of judicial lawmaking becomes more urgent. The 2016 judicial reform did not positively resolve this issue. As of 2024, the need to introduce judicial lawmaking is mostly recognised at the doctrinal level, but the legislating body denies it, although there are various manifestations of the applied use of the lawmaking potential of courts in the national legal system of Ukraine. The practical value of the findings is that the highest authorities of Ukraine can use them to improve the efficiency of lawmaking, justice, and the transformation of the judicial system